COMPATIBILITY OF BIOMAGNETIC PROFILES FOUND IN LIVING MATTER BY CROSS SPECIES DEMONSTRATION - Embi Bs, Abraham A (International Journal of Research -GRANTHAALAYAH, 2018)
Biomagnetic research is the study of living entities (plants or animals) weak magnetic emissions. The purpose of this manuscript is to present a historical review and evolution of techniques introduced with the purpose of demonstrating bioelectromagnetic emissions of living tissue; as well as its potential uses in medical research. This will be accomplished by revisiting prior research papers. The hair follicle has been described as a miniorgan, having cellular divisions, thus metabolism. As previously described “metabolism entails electron transfers in both plants (photosynthesis and respiration) and animals (cellular respiration) involving movement of electrons from donor to acceptor along the electron transfer chain thus inducing a current within each cell and from cell to cell. According to Faraday’s Law and the Hall Effect, these currents induce electromagnetic fields (EMFs) perpendicular and horizontal, respectively, to the plane of the living tissues”. Originally the recordings entailed use of complex magnetic shielding and instrumentation. Recently, two tabletops microscopy techniques were introduced, the first using a Prussian Blue Technique mixed with fine iron particles (2000 nanometers in diameter), the second utilizes a three-tier methodology, where cross species magnetic profiles compatibilities are recorded. The utility and medical applications of the two tabletop techniques are discussed